Case Study of Stormwater Control by Permeable Road in Commercial Centre under Equatorial Climate - Mah, Yau Seng; Norazlina, Bateni; Frederik Josep, Putuhena (UCTEA Turkish Chamber of Civil Engineering, 2023)
This paper describes the investigation into stormwater control measures of a 3,425 m2 commercial centre with 61% of the total areas which were tarred surfaces. Targeting these surfaces, permeable roads of various surface areas from 10 to 34% of the total areas were modelled using Storm Water Management Model version 5.0. Testing the permeable roads for very-short duration storms ranging from 5 to 15 minutes, the study found that the catchment area contributing water for detention purposes played a major role in stormwater control. Other than that, the orifice outlet attached to the storage facility was dominant in determining the flow than the storage depth.